Deep vein thrombosis secondary to an ovarian tumor – approach in low resource settings: A case report - Korel Antonio Hernandez López; David Fernando Pinal Garcia; Aniriam Garcia Arellano; Alejandro Daniel Navarro Alcala (Turkish Journal of Vascular Surgery)
We present a case of a 37-year-old woman who exhibited symptomatic acute deep vein thrombosis (DVT) due to extrinsic compression from a giant ovarian cyst, detected during clinical examination. Doppler ultrasound confirmed a thrombus in the left iliac vein. Although surgery was initially planned to insert a vena cava filter, the absence of this resource during her 14-day hospital stay led to the decision to proceed without it. The surgery was carried out without complications, and she was discharged on the second postoperative day. A 3-month follow-up indicated favorable recovery. [Turk J Vasc Surg 2024; 33(2.000): 115-7]